Dealing with Load Uncertainties and Component Outages in Short Term Marginal Price Computation - João Tomé Saraiva (2003)
In this paper we present a hybrid model to deal with uncertainties affecting nodal marginal prices in transmission networks. The uncertainties addressed are related with loads and component outages. Trapezoidal fuzzy numbers are used to represent load uncertainties and component outages are modeled by probabilistic concepts. This hybridization integrates these uncertainties in a Monte Carlo simulation for which we developed an acceleration technique. This approach can be used to derive target prices in the scope of transmission contracts in order to reduce the volatility of short term marginal tariffs. The developed approach is illustrated with a case study based on the IEEE 24 bus system.